The Effect of Environmental Performance and Green Accounting on Firm Value - Fikriyah, Siti Hailatul; Wiyanti, Rahma (Universitas Pamulang, 2023)
Both large corporations and small and medium-sized businesses frequently ignore environmental problems. However, environmental accounting, known as